Challenges of the Nigerian Banking Sector and the Way Forward - Gololo, Ibrahim Aliyu (American Finance & Banking Review, 2018)
Nigerian banking sector struggle with challenges in the day to day running of their business activities, challenges are enormous and can either be market or operational challenges and regulatory or reforms challenges instituted by the regulatory agencies such as CBN, NDIC, SEC and CIBN etc. Therefore, this paper seeks to examine the challenges facing the Nigerian banking sector and proper possible solutions to the challenges based on the prevailing economic environment. The paper utilized questionnaires as source of data collection, fifteen out of 24 banks were selected based on purposive sampling method. Chi-Square (x2) method was adopted as a statistical tool of data analysis to analyze the collected data.  The result reveals that myriad of challenges exist in the Nigerian banking sector some of which are challenges both within and outside Nigeria. Banks are left behind in technological innovation aspect of banking transactions, movement of high volume of deposit or capital flight to foreign banks by the political class which reduce banks opportunity to expand their market base and the prevalent of fraud in the sector also hinders the banks progress, these challenges affects the sector to compete equally with banking sector in the developed nations. However, we also found that the challenges does not affect their financial performance. It is recommended that that government and relevant regulatory agencies should put heads together to render support and address those challenges identified that affect the sector, also Nigerian banking sector should invest in both technological innovation and human capital development, they should imbibe the culture of good corporate governance and stick to the issue of banking ethics and professionalism among others.